Trade‐offs between biodiversity and agriculture are moving targets in dynamic landscapes [Conjunto de datos] - Macchi, Leandro; Decarre, Julieta; Goijman, Andrea Paula; Mastrangelo, Matías Enrique; Blendinger, Pedro Gerardo; Gavier Pizarro, Gregorio Ignacio; Murray, Francisco; Piquer Rodriguez, María; Semper-Pascal, Asunción; Kuemmerle, Tobias (2020)
Supplementary information of Trade‐offs between biodiversity and agriculture are moving targets in dynamic landscapes. Journal of Applied Ecology (First published: 21 July 2020)